TLR signaling adaptor protein MyD88 in primary sensory neurons contributes to persistent inflammatory and neuropathic pain and neuroinflammation - Liu, Xing-Jun (Sci Rep, 2016)
Increasing evidence suggests that neuro-immune and neuro-glial interactions are critically involved in chronic pain sensitization. It is well studied how immune/glial mediators sensitize pain, but how sensory neurons control neuroinflammation remains unclear. We employed Myd88 conditional knockout (CKO) mice, in which Myd88 was deleted in sodium channel subunit Na(v)1.8-expressing primary sensory neurons, to examine the unique role of neuronal MyD88 in regulating acute and chronic pain, and possible underlying mechanisms. We found that baseline pain and the formalin induced acute inflammatory pain were intact in CKO mice. However, the late phase inflammatory pain following complete Freund’s adjuvant injection and the late phase neuropathic pain following chronic constriction injury (CCI), were reduced in CKO mice. CCI induced up-regulation of MyD88 and chemokine C-C motif ligand 2 expression in DRG neurons and macrophage infiltration into DRGs, and microglia activation in spinal dorsal horns in wild-type mice, but all these changes were compromised in CKO mice. Finally, the pain hypersensitivity induced by intraplantar IL-1β was reduced in CKO mice. Our findings suggest that MyD88 in primary sensory neurons plays an active role in regulating IL-1β signaling and neuroinflammation in the peripheral and the central nervous systems, and contributes to the maintenance of persistent pain.